Forensic Accounting before the Libyan Judiciary as a Mechanism to Reduce Financial Corruption: A Field Analytical Study - Shaitir, Fathya Gebril; Shaitir, Jazia Gebril (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to explore the feasibility of adopting forensic accounting mechanisms to assist the Libyan judiciary in combating financial corruption and to determine the effectiveness of this mechanism in ensuring justice and protecting public funds amid the institutional and legal challenges facing the state. Using a descriptive-analytical approach, data were collected through questionnaires distributed to members of the judiciary who constituted the study sample. The data were analyzed using SPSS software through descriptive statistical tests (frequencies, means, standard deviations) and inferential tests (one-sample t-test and one-way ANOVA). The results showed that between 88% and 98% of judiciary members are aware of the importance of the qualifications and skills required of forensic accountants. Between 63% and 95% recognized the frequent occurrence of financial corruption cases, while 62% to 73% expressed the need for an assisting mechanism to provide necessary evidence in such cases. Additionally, 67% to 90% confirmed the existence of Libyan legislation that permits the engagement of forensic accountants. Based on these findings, the study recommended appointing a sufficient number of competent forensic accountants within the judicial expertise apparatus, dedicating them to criminal cases to assist judicial investigators in evidence gathering and investigation. It also recommended strengthening the Anti-Corruption Prosecution with advanced mechanisms, including appointing forensic accountants within its staff. Furthermore, the study advised allocating specific divisions within criminal courts to handle financial corruption cases to ensure the quality of judicial rulings. It also emphasized coordinating efforts between the Supreme Judicial Council and the Accountants’ Syndicate to establish a joint institute for training forensic accountants and introducing a specialized forensic accounting course in law faculties to enhance accounting literacy among law graduates.
Keywords: forensic accounting; financial corruption; judicial power